Assessing children's social and emotional wellbeing at school entry using the strengths and difficulties questionnaire. (24th May 2012) - White, JM; Barry, S; Marryat, L; McClung, M; Thompson, L; Wilson, P
Abstract : Aim: Emotional and behavioural disorders in early childhood are related to poorer academic attainment and school engagement. In Scotland, most children attend an Early Years establishment from the age of three years prior to transferring to primary education around the age of five years. Initially piloted in 2010, the Strengths and Difficulties Questionnaire (SDQ) has been introduced as a routine part of the transition process for children about to start school. The SDQ assesses emotional, conduct, hyperactivity/inattention, and peer-relationship problems as well as prosocial behaviour. Along with aiding communication about the strengths and difficulties of individual children, the prevalence of emotional or behavioural problems of children starting school in a large local authority area can be assessed. We have examined the feasibility of using this whole population approach. Method: The SDQ was completed by early years staff in local authority and partnership nurseries for children entering primary school in summer 2010 and 2011. Semi-structured interviews (n=25) were conducted with staff in order to explore the process of completing the SDQ along with its perceived value. Parents from a representative sample of establishments were asked to complete the SDQ in order that their ratings could be compared with teachers. Results: We have data from approximately 70% of children starting school in 2010 and 2011. Patterns of problems were similar to UK norms but area effects that require further exploration were identified. Mapping of the prevalence of children's emotional and social functioning by electoral ward will be presented along with findings from the qualitative interviews. In the main, the SDQ was welcomed as an opportunity to highlight children's and emotional development but concerns were raised about the wording of the questionnaire, the potential of 'labelling' a child and the added workload. Concurrent validity data comparing teacher and parent ratings will be presented. Conclusion: Measuring social and emotional wellbeing at school entry may be a useful indication of readiness to learn. We have demonstrated that a whole population approach is feasible.